Autocratic Leadership Style in Higher Education Institutions: a Systematic Literature Review - Nabil, Muhammad Bahrul; Setiyowati, Ninik; Dwiastuti, Ike (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This article aims to map the practices and consequences of autocratic leadership styles in higher education institutions, situating them within the broader context of contemporary leadership in higher education. A systematic literature review was conducted to analyse 19 articles published between 2012 and 2025 within the context of structured higher education. The review process involved the stages of identification, screening, feasibility assessment and inclusion, with the inclusion criteria being relevance to autocratic leadership and to the context of education, and clarity of methodological reporting and outcome indicators. The results of the synthesis show that autocratic leadership is still a reality in many higher education institutions. This is reflected in lower job satisfaction, decreased creativity and initiative, deteriorating quality of working relationships and an increased tendency to leave the institution. However, research on authoritarian elements can contribute to the development of clear command structures, strict procedural compliance, and accelerated decision-making. However, the normative preferences of the academic community are democratic, transformational and participatory leadership. Furthermore, autocratic leadership is difficult to implement in a way that is transparent, ethically sound, and governed well.Artikel ini mengeksplorasi secara komprehensif manifestasi praktik dan konsekuensi psikologis dari gaya kepemimpinan otokratis di perguruan tinggi, dengan menempatkannya dalam lanskap dinamika perilaku organisasi kontemporer. Menggunakan desain systematic literature review (SLR), penelitian ini mengekstraksi data dari 19 artikel empiris terindeks Scopus (periode 2012–2025) yang lolos uji kelayakan dan kriteria inklusi secara ketat, dari total 65 literatur awal yang dihimpun melalui perangkat Publish or Perish. Hasil sintesis mengindikasikan bahwa kepemimpinan otokratis masih terinternalisasi dalam iklim organisasi akademik, yang secara konsisten berkorelasi dengan deteriorasi kepuasan kerja, inhibisi perilaku inovatif, serta eskalasi turnover intention di kalangan staf. Kendati demikian, temuan juga menyoroti fungsi instrumental dari gaya ini seperti akselerasi pengambilan keputusan dan determinasi kepatuhan prosedural terutama pada konteks situasional yang krisis dan menuntut asertivitas regulatif. Walaupun preferensi normatif sivitas akademika tetap berakar pada pendekatan kepemimpinan demokratis dan transformasional, penelitian ini memberikan novelty (nilai kebaruan) melalui sintesis literatur pasca-pandemi yang krusial bagi formulasi model kepemimpinan hibrida. Keterbatasan utama kajian ini mencakup eksklusi literatur non-bahasa Inggris serta tingginya eksposur studi yang didominasi oleh negara-negara berkembang dengan konstelasi budaya jarak kekuasaan tinggi (high power distance).